Factors Affecting Interest of Western Kalimantan Students in Investing in Sharia Capital Markets - Afifah, Khusnul Munawaroh; Anwari, M. Khairul; Sukardi, Sukardi; Anshori, Aiyub (Universitas Muhammadiyah Pontianak, 2023)
The study aims to analyze the factors that influence the interest of Western Kalimantan students in investing in the Sharia capital market. Hypothesis testing using double linear regression analysis methods and classical assumption testing.Sampling techniques used random sampling, with samples taken as many as 100 students. The data used is primary data or direct data that comes from the students who are located in the research. The results of the research found that internally inner urge/internal factors, social motivation factors, emotional factors and peer factors have a positive and significant influence on the interest of Western Kalimantan students in investing in the Sharia Capital Market.